The Role of ORAI1 in the Odontogenic Differentiation of Human Dental Pulp Stem Cells. (November 2015) - Sohn, S.; Park, Y.; Srikanth, S.; Arai, A.; Song, M.; Yu, B.; Shin, K.-H.; Kang, M.K.; Wang, C.; Gwack, Y.; Park, N.-H.; Kim, R.H.
Pulp capping, or placing dental materials directly onto the vital pulp tissues of affected teeth, is a dental procedure that aims to regenerate reparative dentin. Several pulp capping materials are clinically being used, and calcium ion (Ca 2+ ) released from these materials is known to mediate reparative dentin formation. ORAI1 is an essential pore subunit of store-operated Ca 2+ entry (SOCE), which is a major Ca 2+ influx pathway in most nonexcitable cells. Here, we evaluated the role of ORAI1 in mediating the odontogenic differentiation and mineralization of dental pulp stem cells (DPSCs). During the odontogenic differentiation of DPSCs, the expression of ORAI1 increased in a time-dependent manner. DPSCs knocked down with ORAI1 shRNA (DPSC/ORAI1sh) or overexpressed with dominant negative mutant ORAI1 E106Q (DPSC/E106Q) exhibited the inhibition of Ca 2+ influx and suppression of odontogenic differentiation and mineralization as demonstrated by alkaline phosphatase (ALP) activity/staining as well as alizarin red S staining when compared with DPSCs of their respective control groups (DPSC/CTLsh and DPSC/CTL). The gene expression for odontogenic differentiation markers such as osteocalcin, bone sialoprotein, and dentin matrix protein 1 ( DMP1 ) was also suppressed. When DPSC/CTL or DPSC/E106Q cells were subcutaneously transplanted into nude mice, DPSC/CTL cells induced mineralized tissue formation with significant increases in ALP and DMP1 staining in vivo, whereas DPSC/E106Q cells did not. Collectively, our data showed that ORAI1 plays critical roles in the odontogenic differentiation and mineralization of DPSCs by regulating Ca 2+ influx and that ORAI1 may be a therapeutic target to enhance reparative dentin formation.